Investigation of ethnomathematics approach for mathematics learning in islamic schools - Arsyil Waritsman; Rita Lefrida (12 Waiheru, 2024)
The study aims to systematically investigate the use of an ethnomathematics approach in teaching mathematics in Islamic schools. The method used is a systematic literature review on phases including identification, screening, feasibility assessment, and inclusion. The usage of the method in this study shows several findings namely (1) The ethnomathematics research in Islamic schools was mostly conducted in Central Java Province; (2) The ethnomathematics approach has been implemented, developed, and effectively applied to mathematics learning in Islamic schools; (3) The ethnomathematics approach has significant benefits which are improving the outcomes of students’ learning, initiating a more effective and enjoyable learning, and stimulating a love of the culture to the students; (4) Research approaches used in the ethnomathematics approach in Islamic schools were diverse such as quantitative, qualitative and developmental approaches (5) The method used to evaluate the effectiveness of the ethnomathematics approach were giving exams, administering questionnaires and interviews; (6) Most of the topics discussed in the ethnomathematics approach in Islamic schools was geometry, while the culture discussed regarding mathematics learning was various. The results of this systematic literature review study will enrich the information on educational development, especially culture-based mathematics learning, known as ethnomathematics.